Pemetaan Kerusakan Jalan dengan Metode Pavement Condition Index pada Ruas Jalan Arteri Mojosari-Mojokerto Berdasarkan Sistem Informasi Geografis - Albar, Aldino Maulana; Wibisana, Hendrata (Universitas Batanghari Jambi, 2026)
Road infrastructure plays an important role in supporting community mobility and economic growth in a region. The Mojosari–Mojokerto arterial road has experienced various types of damage due to increased vehicle volume, especially heavy trucks, which has led to an increased risk of accidents. This study aims to determine the level of pavement damage on the Mojosari–Mojokerto road section using the Pavement Condition Index (PCI) method and to map the condition of road damage with the help of a Geographic Information System (GIS). The research method included a field survey conducted on April 4–22, 2025, from 8:00 a.m. to 5:00 p.m. to collect primary data on the type, dimensions, and level of road damage. The analysis was carried out by calculating the PCI value using the formula PCI = 100 – CDV, then the results were visualized in the form of thematic maps using ArcMap 10.8 software. The results showed PCI values for several road sections, namely Jalan Raya Airlangga 76, Jalan Raya Gajah Mada 80.5, Jalan Raya Pekukuhan 81.33, Jalan Ahmad Yani 82, and Jalan Raya Ngranggon 79.3, all of which were classified as very good based on the value range of 71–85. In conclusion, the condition of the road pavement on the Mojosari–Mojokerto section is generally still very good, but routine maintenance is still needed, especially on segments with heavy vehicle loads, so that the service life of the road can be extended.